(untitled) (Psychology Travelogs, 2025)
The article focuses on the interrelation between the improvement of the system of personal resources management and the effectiveness of the manager’s professional activity. The role of emotional leadership of a manager in the process of improving the management of personal resources of subordinates is substantiated. The essence and content of theories of emotional intelligence, which are the basis of emotional leadership of a manager, are generalised. A comparative analysis of the interpersonal and intrapersonal types of emotional intelligence in groups of managers differing in the effectiveness of interpersonal and business interaction according to the staff’s assessment has revealed the presence of statistically significant reliable differences. A comparative analysis of intrapersonal and interpersonal types of emotional intelligence in groups of managers who differ in the effectiveness of business and interpersonal interaction according to staff assessments has revealed statistically significant differences. The group of managers who received high marks (the first group), compared to the groups of managers who received medium (the second group) and low (the third group) staff assessments, is characterised by a high level of interpersonal emotional intelligence, intrapersonal emotional intelligence, understanding and management of emotions. Managers in the first group have more developed abilities to understand their own emotions and the emotions of others, as well as to manage their own and other people’s emotions. The second and third groups of managers are characterised by statistically significant differences only in the level of managing their own and other people’s emotions. The level of development of intrapersonal and interpersonal types of emotional intelligence, understanding of own and other people’s emotions is in the range of average values with no statistically significant differences. The emotional leadership potential of the heads of teaching teams who received low scores on the effectiveness of interpersonal and business interaction is limited by the lower level of development of managing their own and other people’s emotions.